2023
DOI: 10.1021/acs.est.3c01941
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidative Coupling of Methane to Ethane Using Water and Oxygen on Ag3PO4-ZnO

Abstract: Photocatalytic oxidative coupling is an effective way of converting CH4 to high-value-added multi-carbon chemicals under mild conditions, where the breaking of the C–H bond is the main rate-limiting step. In this paper, the Ag3PO4-ZnO heterostructure photocatalyst was synthesized for photocatalytic oxidative coupling of methane (OCM) to C2H6. In addition, an excellent C2H6 yield (16.62 mmol g–1 h–1) and a remarkable apparent quantum yield (15.8% at 350 nm) at 49:1 CH4/Air and 20% RH are obtained, which is more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Therefore, the effects of reaction temperature and Au plasmon resonance on the OCM reaction were excluded out for Au/TiO 2 –NV o catalysts. Numerous studies have also confirmed that the performance of OCM depends mainly on light irradiation rather than temperatures less than 150 °C. ,, We also tested the performance of the catalyst under simulated light conditions (AM 1.5G), the catalyst can also exhibit C 2 H 6 yields of 1.76 μmol h –1 (Figure S20a). The yield was significantly decreased due to the much smaller proportion of ultraviolet bands in the simulated 1sun as compared to the original xenon lamp (Figure S20b).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the effects of reaction temperature and Au plasmon resonance on the OCM reaction were excluded out for Au/TiO 2 –NV o catalysts. Numerous studies have also confirmed that the performance of OCM depends mainly on light irradiation rather than temperatures less than 150 °C. ,, We also tested the performance of the catalyst under simulated light conditions (AM 1.5G), the catalyst can also exhibit C 2 H 6 yields of 1.76 μmol h –1 (Figure S20a). The yield was significantly decreased due to the much smaller proportion of ultraviolet bands in the simulated 1sun as compared to the original xenon lamp (Figure S20b).…”
Section: Resultsmentioning
confidence: 99%
“…And the Ag nanoparticle supporting on the ZnO further increased the photoactivity due to the surface plasmon resonance. Wang et al [131] synthesized a Ag 3 PO 4 -ZnO hetero-structured photocatalyst for OCM reaction, which exhibited excellent C 2 H 6 yield (16.62 mmol•g À 1 •h À 1 ) and significant apparent quantum yield (15.8 % at 350 nm). It was suggested that Ag 3 PO 4 improved the adsorption and dissociation ability of O 2 and H 2 O, which were conducive to the formation of surface hydroxyl group.…”
Section: Photocatalytic Oxidative Coupling Of Methanementioning
confidence: 99%